Effects of speed on plantar forces in three-foot regions during treadmill walking: A preliminary study using force sensing insoles - Nakanowatari Tatsuya; Ishiya Syunsuke; Sato Shuka; Kanzaki Hideto (Sciendo, 2024)
Study aim: The foot has region-specific biomechanical functions for absorbing shock, however, the effects of walking speed on plantar forces in the foot regions are unknown. The purpose of this study was to investigate the measurement repeatability and changes of regional (forefoot, midfoot, and rearfoot) plantar force by a triple-sensor wireless insole by gait speed modifications during treadmill walking.